The Rise of Citizen Journalism: Opportunities and Challenges - Wang, Zejun (Journal of Theory and Practice of Engineering Science, 2023)
With the global popularisation of internet technology and the rise of social media, citizen journalism has become a widely discussed and rapidly developing form of news communication. Citizen journalism provides a platform for ordinary people to make their voices heard, making news reports more diversified and rich. In addition, the theoretical basis of citizen journalism includes civil society theory, participatory culture theory, public sphere theory, audience theory, etc., which lays the foundation for the development of citizen journalism. At present, citizen journalism has become an important part of journalism, providing the public with abundant news information. This paper aims to explore the conditions under which citizen journalism develops vigorously, analyze the characteristics, advantages and existing problems behind it, as well as its historical conditions and theoretical basis, in order to provide useful references for the future development of citizen journalism.